1995
DOI: 10.1002/marc.1995.030160102
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective isotactic alternating copolymerization of styrene and 4‐methylstyrene with carbon monoxide catalyzed by a cationic bioxazoline pd(II) complex

Abstract: The cationic bioxazoline Pd(I1) complex 2 catalyzes the alternating copolymerization of carbon monoxide with styrene and 4-methylstyrene, respectively, to yield a highly isotactic optically active polymer at room temperature and low carbon monoxide pressure (1 -4 atm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 12 publications
4
56
1
Order By: Relevance
“…In a previous paper in which some of the same ligands employed here had been tested, it had been noted that a higher productivity was obtained with unsubstituted styrene, 17 contrary to what was generally reported in the literature. 39,[40][41][42][43] The new, more extensive, series of data supports this observation, but also shows that the higher activity is also associated with a faster deactivation, since not only k 1 , but also k 3 values are consistently higher in the case of styrene. To the best of our knowledge, an active role of the olefin in the deactivation process has not been proposed before.…”
Section: Fitting Of the Data Of The Styrene Experiments Run Under 5 Bsupporting
confidence: 58%
“…In a previous paper in which some of the same ligands employed here had been tested, it had been noted that a higher productivity was obtained with unsubstituted styrene, 17 contrary to what was generally reported in the literature. 39,[40][41][42][43] The new, more extensive, series of data supports this observation, but also shows that the higher activity is also associated with a faster deactivation, since not only k 1 , but also k 3 values are consistently higher in the case of styrene. To the best of our knowledge, an active role of the olefin in the deactivation process has not been proposed before.…”
Section: Fitting Of the Data Of The Styrene Experiments Run Under 5 Bsupporting
confidence: 58%
“…[12] The phosphino-phosphite BINAPHOSl igand was found to be able to promote the copolymerization of carbon monoxide with both propene and styrene. [13,14] Focusingt he discussion on aromatic alkenes, the researches published up to now allowed establishing ar elationship between the symmetry of the bidentate N-donor ligand in the palladium catalyst andt he copolymer stereochemistry.P d complexes with C 2v symmetric ligands, such as 2,2'-bipyridine [15] and 1,10-phenanthroline, [16] afforded syndiotactic polyketones,w hereas Pd derivatives with enantiomerically pure C 2 symmetric ligands, such as bi-or bis-oxazolines, [17][18][19] aza bisoxazolines, [20] and diketimines [21] led to the formationo fisotatic copolymers. C s ligands have been reported to yield both syndio-and atacticp olyketones, [22] whereas all the possible microstructures can be obtained by using C 1 ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The higher incorporation of 4-tert-butylstyrene over ethylene found for the cationic catalysts 1b-3b, could therefore be ascribed to the modest steric hindrance offered from this class of C s symmetrical ligands. Additional analysis by means of 13 [17,18,34,39] which indicates complete stereoregularity. The signal at 45.4 ppm was attributed to isolated CO/TBS units [19].…”
Section: Catalytic Co/tbs Copolymerizationmentioning
confidence: 99%
“…Among the higher olefins, vinylarenes have gained most attention as comonomers. Most of the results with styrene and derivatives have been obtained with catalysts based on ligands developed for the stereocontrolled co-and terpolymerization [13][14][15][16][17][18][19][20][21][22][23][24][25], as for N-N [13][14][15][16][17], P-N [18,19], N-N 0 [25] and P-O [23]. Furthermore, it has been shown that catalytic tests performed in 2,2,2-trifluoroethanol (TFE) as solvent, greatly improved catalyst lifetime leading to higher productivities and molecular weights [26].…”
Section: Introductionmentioning
confidence: 99%